Menachem Begin : a life - Shilon, Avi (Yale University Press, 2012)
Menachem Begin, father of Israel's right wing and sixth prime minister of the nation, was known for his unflinchingly hawkish ideology. Through Begin's remarkable life, this book also recounts the history of the right-wing segment of Israeli society, a story essential to understanding the Israel of today.